A Usage-Based Proposal for Argument Structure of Directional Verbs in American Sign Language - Hou, Lynn (Frontiers in Psychology, 2022)
Verb agreement in signed languages has received substantial attention for a long time. Despite the numerous analyses about the linguistic status of verb agreement, there is little discussion about the argument structure associated with ‘directional verbs’, also known as agreeing/agreement or indicating verbs. This paper proposes a usage-based approach for analyzing argument structure constructions of directional verbs in American Sign Language (ASL). The proposal offers low-level constructions for reported speech, non-dedicated passive and reflexive, and stance verb constructions, which capture the patterns, abstracted from recurring usage events, that are part of users’ linguistic knowledge. The approach has potential to push the field of sign linguistics in new directions of understanding the interplay of language use and structure.